Calidad de adn de personas impactadas por la minería artesanal en el cerro el toro, huamachuco, la libertad 2010 - Casanova Herrera, Hugo Enrique (2013)
The present research work is to determine the toxic substances and DNA damage for people impacted by artisanal mining of Cerro El Toro, using the comet assay. Knowing that at present the impact of mining is a problem that affects the global environment and to Peru by the. gold mining in people causing health problems that could reach various cancer diseases, caused by a genotoxic effect of the chemicals used in mining affecting chromosomal DNA. Atomic absorption spectroscopy was used as a method to determine the metals in soil and water impacted by mining and the comet assay for the determination of genotoxic effects in DNA. It was possible to determine the presence of mercury in soil and water, iron, copper and lead in soil, water cyanide and arsenic in soil and water as well as the genotoxic effect in the DNA of people impacted by artisanal mining of Cerro El Toro finding 77.78% of the samples show negative, and 22.22% have DNA damage, being determinants exposure time and the type of contact, showing DNA damage through microscopic observation by entering Effect Comet metals the organism by different routes of absorption and accumulate in adipose tissues, being difficult to remove from the body, causing chemical reactions in time and functional group transformations causing the disintegration of the DNA.